Mimicry and honesty: people give more honest responses to their mimicker - Nicolas Guéguen (Universidad de San Buenaventura, 2013)
Mimicry is generally associated with a positive perception of the mimicker. Our hypothesis stated that participants would become more honest in their responses to a survey administered by a mimicking interviewer. Students were invited to participate in a survey on their ecological behavior. During the first part of the survey, the ‘experimental confederate’ either mimicked their interlocutor or did not. It was found that participants declared less ecological behavior in their everyday life in the mimicry condition than in the non-mimicry condition.